National Spatial Planning in Regional Development - Lisdiyono, Edy (Lex Publica, 2020)
Planning is a tool to increase the added value of available resources in an area or region to increase the community's welfare as much as possible within a certain period. Regional spatial planning is concerned with the efficient and effective use of natural resources and the allocation of space for activities by the carrying capacity of the natural environment and the capacity of the built environment, taking into account human resources and community aspirations. This study uses a research method that refers to legal theories to develop study-oriented arguments for spatial planning in border areas. Based on the issues raised in this study is doctrinal (normative) research, using a normative legal research approach through a statutory approach (statute approach). Considering the existing government organizational structure, controlling the use of space is not sufficient only to be handled by elements of the regional government but must include the judiciary (prosecutors & judiciary), legislature, and police, according to the substance of the problem. Spatial planning must adopt a participatory approach through community participation in every stage. Spatial planning, on the other hand, can not only be seen from the side of the product of the regional spatial plan but must also be seen from the operationalization of the policy into space utilization and spatial use control. Abstrak Perencanaan merupakan suatu alat untuk meningkatkan nilai tambah sumber daya yang tersedia dalam suatu wilayah atau daerah dalam rangka mencapai tujuan peningkatan kesejahteraan masyarakat yang sebesar-besarnya dalam kurun waktu tertentu. Perencanaan tata ruang wilayah berkaitan dengan upaya pemanfaatan sumber daya alam secara efisien dan efektif, serta alokasi ruang untuk kegiatan yang sesuai dengan daya dukung lingkungan alam dan daya tampung lingkungan binaan, dengan memperhatikan sumber daya manusia serta aspirasi masyarakat. Penelitian ini menggunakan metode penelitian yang mengacu pada teori-teori hukum dengan tujuan untuk mengembangkan argumen kajian yang berorientasi pada pengaturan terhadap rencana tata ruang di daerah perbatasan. Berdasarkan permasalahan yang diangkat dalam penelitian ini adalah penelitian doktrinal (normatif), menggunakan metode pendekatan penelitian hukum normatif melalui pendekatan perundang-undangan (statute approach). Memperhatikan struktur organisasi pemerintahan yang ada, pengendalian pemanfaatan ruang tidak cukup hanya ditangani oleh unsur pemerintah daerah saja, tetapi harus mencakup lembaga yudikatif (kejaksaan & kehakiman), legislatif serta kepolisian, disesuaikan dengan substansi permasalahannya. Penataan ruang harus sudah mengadopsi pendekatan partisipatif, melalui peran serta masyarakat dalam setiap tahapannya. Penataan ruang dilain pihak, tidak hanya dapat dilihat dari sisi produk rencana tata ruang wilayahnya saja, tetapi juga harus dapat dilihat dari operasionalisasi kebijakan tersebut ke dalam pemanfaatan ruang maupun pengendalian pemanfaatan ruang. Kata kunci: Perencanaan, Tata Ruang, Kebijakan, Pembangunan, Daerah